Taming the river : negotiating the academic, financial, and social currents in selective colleges and universities - Charles, Camille Zubrinsky, 1965- (Princeton University Press, 2009)
Building on their important findings in The Source of the River, the authors now probe even more deeply into minority underachievement at the college level. Taming the River examines the academic and social dynamics of different ethnic groups during the first two years of college. Focusing on racial differences in academic performance, the book identifies the causes of students' divergent grades and levels of personal satisfaction with their institutions. Using survey data collected from twenty-eight selective colleges and universities, Taming the River considers all facets of student life, in.